Widening income inequalities in life expectancy? Analysing time trends based on German health insurance data. Issue 7 (10th April 2020) - Tetzlaff, Fabian; Epping, Jelena; Sperlich, Stefanie; Tetzlaff, Juliane
Abstract : Background: While social disparities in mortality have been shown in the majority of high-income countries, research on inequalities in the German population is still limited. This applies especially to studies investigating time trends in social inequalities with respect to life expectancy. The aim of this study is to examine income inequalities in life expectancy and whether inequalities have narrowed or widened over time. Methods: The analyses are based on the claims data of a large German health insurance provider, which facilitates the combining of information on individual income and mortality. Life expectancy is calculated separately for three income groups (<60%, 60% to 80% and ≥80% of the average income in Germany) and for sex by applying period life table analyses. Trends are assessed by comparing the time periods 2005–2008 (N = 1 773 122), 2009–2012 (N=1 792 735) and 2013–2016 (N = 1 987 114). Results: Trends in life expectancy differed by sex, age and income group. Especially among elderly men, the gap between low- and high-income groups widened over time, disadvantaging men with low incomes. Among women, a slight reduction in inequalities was observed, which was driven by the increases in life expectancy in low-income groups. Conclusion: Our study shows that not all population subgroups benefitted equally from the continuing rise in life expectancy. The persisting inequalities emphasise the importance of public health efforts concentrating on reducing mortality risks among individuals in lower socioeconomic positions. Special attention should be paid to elderly men with low incomes. Further research is needed on the mechanisms underlying increasing health inequalities over time.